Recent Advances in the Indonesian Paediatric Gastroenterology
Recent advances in the Indonesian Paediatric Gastroenterology have been presented in the 4 following headings and conclusions : (1)’ROSE’ system as the principle of treatment of diarrhoea, which is proven to be effective and gives an excellent result in reducing the case fatality rate of acute gastroenteritis, especially cholera. (2) MCT and low lactose containing formula in low birth weight infants gives good to excellent results in improving fat malabsoprtion, ceasing the diarrhoea and increase of body weight. (3